(untitled) (REVELL - REVISTA DE ESTUDOS LITERÁRIOS DA UEMS, 2020)
This paper aims to analyze racist discourses and identity aspects in the novel Americanah (2013), written by Chimamanda Ngozi Adichie. The main objectives of this research are to identify the impacts immigration brought to the protagonist’s social and personal life and to determine how her identity construction was affected by stereotypes and social structure. The methodology used in this study was a bibliographical research. The work is divided into two sections: firstly, a literature review, explaining theories on Critical Discourse Analysis, identity and racism, developed by authors such as Beale (1970), Smit (1996), Fairclough (2009) and Feagin (2014); afterwards, a critical analysis of excerpts and dialogues extracted from the book.